2016
DOI: 10.1055/s-0042-100903
|View full text |Cite
|
Sign up to set email alerts
|

Refractory strictures despite steroid injection after esophageal endoscopic resection

Abstract: Background: Although steroid injection prevents stricture after esophageal endoscopic submucosal dissection (ESD), some patients require repeated sessions of endoscopic balloon dilation (EBD). We investigated the risk for refractory stricture despite the administration of steroid injections to prevent stricture in patients undergoing esophageal ESD. Refractory stricture was defined as the requirement for more than three sessions of EBD to resolve the stricture. In addition, the safety of steroid injections was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 22 publications
1
60
3
Order By: Relevance
“…We use relatively low doses over a limited period and it seems unlikely that this has an impact in the long term. Moreover, the stricture rate increases drastically when 75% of the circumference is involved [20] and in our study 24/31 patients underwent circumferential resection in 2 to 3 sessions (Table 1). The other patients (7/31) underwent resection in 1 session of esophageal mucosa larger than the half-circumference, but less than 75% of the esophageal lumen (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…We use relatively low doses over a limited period and it seems unlikely that this has an impact in the long term. Moreover, the stricture rate increases drastically when 75% of the circumference is involved [20] and in our study 24/31 patients underwent circumferential resection in 2 to 3 sessions (Table 1). The other patients (7/31) underwent resection in 1 session of esophageal mucosa larger than the half-circumference, but less than 75% of the esophageal lumen (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…Local TA injection for noncircumferential lesions showed favorable outcomes in some studies, whereas stricture rates were rather high in other studies (Table ) . In the assessment of treatment efficacy, extent of mucosal defect may affect stricture rates.…”
Section: Steroid Therapymentioning
confidence: 99%
“…In one clinical study, a deep submucosal tear without perforation occurred when the endoscope was passed through the narrow space formed by the post‐ESD scar in a patient who received local TA injection . Other authors have reported a higher risk of perforation in balloon dilation among patients undergoing steroid treatment . Careful balloon dilatation, such as that using a small‐caliber balloon or low inflation pressure, is advised after steroid treatment.…”
Section: Steroid Therapymentioning
confidence: 99%
See 2 more Smart Citations